THE CORRELATION BETWEEN GRAMMAR MASTERY AND WRITING ABILITY - I Gusti Agung Putri Wirastuti; I Ketut Wardana; Ni Made Widiani (Journal on Studies in English Language Teaching (JOSELT), 2022)
The correlation between grammar mastery and writing ability was the purpose of this research study. To conduct this research, the data has collected by the researcher by using correlational research. In collecting the data, the researcher used instrument. The sample were 31 students of the eight grade students of SMPN 4 Mengwi. Quantitative data was used to apply in technique analyzing data. To get the data, the researcher used Pearson Product Moment and the data was taken from grammar and writing test. From the result showed rxy is (0.462) which that in the medium correlation. It means that null hypothesis (Ho) in this research was rejected and the alternative hypothesis (Ha) is accepted. It can be said that, the students with grammar mastery will be easier to writing ability. From the result it can be concluded that there was a positive correlation between grammar mastery and writing ability.